2014
DOI: 10.1093/rheumatology/keu165
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid arthritis-related interstitial lung disease: associations, prognostic factors and physiological and radiological characteristics--a large multicentre UK study

Abstract: This is the largest study of RA-ILD in the UK. Anti-CCP antibodies were strongly associated with RA-ILD in both sexes. Smoking was strongly associated with ILD in males, which may explain the higher frequency of RA-ILD in men. The predominant HRCT pattern was UIP and most patients had limited disease at presentation. The presence of UIP and extensive disease are associated with increased mortality. Baseline gas transfer is a useful screening tool for ILD, while the preservation of VC at baseline might predict … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

37
315
12
20

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 441 publications
(384 citation statements)
references
References 38 publications
37
315
12
20
Order By: Relevance
“…However, it may also suggest some degree of heterogeneity in risk based on the underlying disease diagnosis. Even though we included other ILD diagnoses with IPF in this study, outcomes in end-stage fibrotic lung disease that is not IPF has been demonstrated to be comparable [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…However, it may also suggest some degree of heterogeneity in risk based on the underlying disease diagnosis. Even though we included other ILD diagnoses with IPF in this study, outcomes in end-stage fibrotic lung disease that is not IPF has been demonstrated to be comparable [3][4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…Некоторые авторы указывают на мужской пол в чис-ле факторов риска развития интерстициального ПЛ [7,8,16,19], в то время как другие исследователи это не под-тверждают. Среди наших пациентов преобладали женщи-ны (90%), при этом все мужчины (10%) имели ПЛ.…”
Section: Discussionunclassified
“…Стоит отметить, что аналогичные результаты получили и другие исследователи [1,19]. Так, в работе Y. Yin и соавт.…”
Section: Discussionunclassified
“…Interstitial Lung Disease (ILD) is the only complication of RA reported to be increasing in prevalence (Bongartz et al 2010). In a study by Kelly et al, 47% of deaths in patients with RA associated ILD (RA-ILD) were directly due to ILD (Kelly et al 2014).…”
Section: Dpld In Ramentioning
confidence: 99%